Attenuation of glycation-induced multiple protein modifications by Indian antidiabetic plant extracts - Rashmi S. Tupe; Nisha G. Kemse; Amrita A. Khaire; Shamim A. Shaikh (Taylor & Francis Group, 2017)
Context: Protein glycation is the major contributing factor in the development of diabetic complications. The antiglycation potential of medicinal plants provides a promising opportunity as complementary interventions for complications. Objective: To investigate the antiglycation potential of 19 medicinal plants extracts using albumin by estimating different indicators: (1) glycation (early and late), (2) albumin oxidation, and (3) amyloid aggregation. Materials and methods: The effect of aqueous plant extracts (1% w/v) on protein glycation was assessed by incubating albumin (10 mg/mL) with fructose (250 mM) for 4 days. Degree of protein glycation in the absence and presence of plant extracts was assessed by estimating fructosamine, advanced glycation end products (AGEs), carbonyls, free thiol group and β-amyloid aggregation. Results: Petroselinum crispum, Boerhavia diffusa, Terminalia chebula, Swertia chirayita and Glycyrrhiza glabra showed significant antiglycating activity. P. crispum and A. barbadensis inhibited the carbonyl stress and protected the thiol group from oxidative damage. There was significant correlation between protein thiols and amyloid inhibition (R = −.69, p < .001). Conclusion: P. crispum, B. diffusa and T. chebula had the most potent antiglycation activity. These plant exerted noticeable antiglycation activity at different glycation modifications of albumin. These findings are important for identifying plants with potential to combat diabetic complications.